Ice core evidence for climate change in the Tropics: implications for our future - Thompson, L. G. (Quaternary Science Reviews, 2000)
Reliable meteorological observations for climate reconstruction are limited or absent prior to A.D. 1850 for much of the Earth and particularly in both tropical South America and the Tibetan Plateau region of central Asia. Over 50% of the Earth's surface lies between 30 degrees N and 30 degrees S and 75% of the world's inhabitants live and conduct their activities in these tropical regions. Thus, much of the climatic activity of significance to humanity, such as variations in the occurrence and intensity of the El Nino-Southern Oscillation and monsoons, are largely confined to lower latitudes. Moreover, the variability of these tropical systems and particularly that of the tropical hydrological system in response to regional and global climate forcing are not well understood. Fortunately, ice core records are also available from selected high altitude, low and mid-latitude ice caps. The ice core studies described here were undertaken as part of a long-term program to acquire the global-scale, high-resolution climatic and environmental history essential for understanding more fully the linkages between the low and the high latitudes. Two ice core records, one covering the last full glacial cycle from the Guliya Ice Cap, China (35 degrees N; 6200 m asl) and one from Huascaran, Peru, which reveal significant cooling during the Last Glacial Cycle Maximum (LGM similar to 20,000 yr BP) are compared with preliminary data coming from the new Sajama, Bolivia (18 degrees S, 6550 m asl) and the Dasuopu, Himalaya (China, 28 degrees N, 7200 m asl) cores. Lower delta(18)O values (equivalent to cooling of similar to 8 degrees C) contribute to the growing body of evidence that the tropical climate was cooler and more variable during the last glacial cycle and has renewed current interest in the tropical water vapor cycle. The new tropical ice core records raise additional questions about our understanding of the role of the tropics in global climate. Unfortunately, as a result of recent warming, all known tropical glaciers and ice caps are retreating and soon will no longer continue to preserve viable paleoclimatic records. The characteristics of the current warming will be examined and compared to earlier periods of climatic warming such as the transition form the last glacial into the current interglacial as well as other periods within the Holocene. It is important to distinguish natural variation in the climate system from the anthropogenic influences superimposed during the: last century. These tropical ice cores offer long-term perspectives of accumulation, temperature, atmospheric dust and "greenhouse" gas concentrations against which recent variations may be assessed, with particular relevance for lower latitude regions where most people live. (C) 1999 Elsevier Science Ltd. All rights reserved.
268pvTimes Cited:145Cited References Count:54